1983
DOI: 10.1021/jm00358a007
|View full text |Cite
|
Sign up to set email alerts
|

Conjugates of catecholamines. 1. N-Alkyl-functionalized carboxylic acid congeners and amides related to isoproterenol

Abstract: A series of functionalized catecholamines (congeners) has been synthesized in which, formalistically, the N-isopropyl group of isoproterenol has been extended by a linear alkyl chain of varying length, terminated by a carboxy group or a substituted amide. The compounds were prepared generally via the reductive amination of norepinephrine with a keto acid or a preformed keto amide. An alternate synthesis of the model amide derivatives, involving activation of the carboxylic acid congeners and coupling with amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 2 publications
0
16
0
Order By: Relevance
“…For example, N -protected α-amino aldehydes are important starting materials in organic synthesis [18] and in the asymmetric synthesis of heterocyclic compounds [19]. Aldehydes and ketones are used in peptidomimetic design to form reduced peptide bonds, [CH 2 NH], in the hope of generating compounds with increased metabolic stability [20][21][22]. Aldehyde functionality is also used in preparing larger peptides through ligation strategies, including oxime [23,24] and hydrazone ligations [25], as well as a chemoselective ligation method that forms pseudoproline-containing peptides [26].…”
Section: Introductionmentioning
confidence: 99%
“…For example, N -protected α-amino aldehydes are important starting materials in organic synthesis [18] and in the asymmetric synthesis of heterocyclic compounds [19]. Aldehydes and ketones are used in peptidomimetic design to form reduced peptide bonds, [CH 2 NH], in the hope of generating compounds with increased metabolic stability [20][21][22]. Aldehyde functionality is also used in preparing larger peptides through ligation strategies, including oxime [23,24] and hydrazone ligations [25], as well as a chemoselective ligation method that forms pseudoproline-containing peptides [26].…”
Section: Introductionmentioning
confidence: 99%
“…These inhibitory properties result from the tetrahedral hydrated C‐terminus aldehyde function that mimics the transition state of the substrate during hydrolysis. Moreover, peptide aldehydes are also interesting starting materials for further chemistry upon the aldehyde function—for example, the generation of reduced bond isosteres 5. The second part of this review will focus upon the importance of aldehyde and keto chemistry for the site‐specific modification of peptides and proteins, and for protein engineering in general.…”
Section: Introductionmentioning
confidence: 99%
“…Unique P-adrencrgic ago nists derived from ISO have been developed through conjugation of the parent drug via a spacer group to an anilide-based peptide car rier moiety ( fig. 1) [1], The purpose of this derivatization was to improve the com pound's effect specificity and tissue selectiv ity, to achieve a prolonged duration of action and (potentially) to make oral administra tion possible. Although the original inten tion was to link these compounds to carriers such as peptides and monoclonal antibodies for tissue (and effect) targeting, the model congeners themselves displayed many of the desired improved characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Previous in vitro studies have shown that 119 and 143 are orders of magnitude more potent than ISO in the stimulation of cyclic adenosine monophosphate (cAMP) accumu lation in S49 mouse lymphoma cells [1][2][3][4][5] and that 143 is a more potent positive ino tropic agent than ISO as measured in an iso lated guinea pig atria preparation [2,5], In addition, in this preparation, 143 appeared to have preferential inotropic versus chrono tropic effects. The inotropic effect of 143 also persisted much longer than that ob served with ISO.…”
Section: Introductionmentioning
confidence: 99%